AN AUXILIARY SUGGESTION TO REALIZATION OF RURAL DEVELOPMENT IN AĞIN DISTRICT: RURAL TOURISM - Çelik, Özlem Çakar (My University, 2022)
Ağın is a settlement where tourism and recreational activities are not developed.\rHowever, it has natural and human attractions that can lead to tourism and recreational\ractivities. At the same time, other settlements in its vicinity such as Arapgir, Kemaliye\rand Keban, which have similar geographical conditions, are active in terms of recreational\ractivities and tourism. The construction of Keban Dam Lake is a turning point for Ağın.\rWhile the population growth trend was positive until that time, it entered a continuous\rdecreasing trend with the construction of the dam. The area lost a significant part of its\rfertile rural lands and pasture areas with the construction of the dam. With the\rconstruction of Keban Dam Lake, the area gained the feature of a peninsula. However,\rthe attraction created by water resources, rich cultural and historical background could\rnot do the groundwork for development of tourism activities. In this study, the natural\rand human properties of Ağın were examined in the light of the literature, and these\rfeatures were detailed with field observations. The study concluded that rural tourism is\ran important opportunity for Ağın. It is expected that thanks to rural tourism, population\rloss would decline in the study area while population growth would be achieved in the\rlong run and new employment areas would be opened among the expected benefits.\r
Keywords: Otelcilik; Konaklama; Spor ve Turizm; Çevre Çalışmaları; Coğrafya